Risk stratification for acute stroke development after a transient ischemic attack and the use of scoring systems in pre-hospital scenarios - Janković Tamara; Đorđević Stefan (Halo 194)
Introduction:Transient Ischemic Attack (TIA) is a temporary cerebral circulation disorder manifested by a neurological deficit that usually resolves within 60 minutes, as opposed to cerebrovascular insult, where the cerebral circulation disorder is permanent, and the neurological deficit doesn't resolve. The ABCD2 and Ottawa scores aim to predict the risk of cerebrovascular insult development after TIA. Objective: The objective of this paper is a retrospective analysis of the ABCD2 and the Ottawa score implementation on a patient with a positive history of TIA, the sensitivity analysis of the scores and stressing the importance of standardising their implementation in out-of-hospital scenarios. Case report: The Institute for Emergency Medicine in Belgrade received a call regarding a 68-yearold woman suspected of developing a cerebrovascular insult. We learned heteroanamnestically that the symptoms had been present for more than an hour and that she had similar complaints 4 days ago, but then the symptoms only lasted for about 15 minutes. By the time the Emergency Medical Team arrived, the symptoms had receded, and the patient refused to be taken to the hospital for further analysis. Upon examination, the patient was found to be disoriented and dysphasic, with left hemiparesis and ataxia. This time, the patient was taken to an appropriate hospital, where cerebrovascular insult was confirmed, and she was hospitalised. According to data from the medical report filled out four days earlier, the value of her ABCD2 score was 6, which represents an 11.7% risk of developing a stroke within the next 7 days. The Ottawa score value at the same time was 10 points, representing a 5.1% risk of developing a stroke within the next 7 days. Conclusion: Implementing ABCD2 and the Ottawa scores to predict the impending risk of cerebrovascular insult development in patients with transient ischemic attacks can be helpful. They aid emergency physicians in correctly recognising the early signs and symptoms, reaching a timely diagnosis, and preventing the development of cerebrovascular insult after TIA. This is crucial because for patients who receive adequate therapy, 80% of cerebrovascular insults after TIA can be prevented.